Management of Scientific Information for Agricultural Research in Small Countries: Highlights of a Meeting - International Service for National Agricultural Research (International Service for National Agricultural Research, 1992)
This report highlights the main discussions and conclusions from a meeting of agricultural information specialists from small countries. The meeting was part of an ISNAR project on strategies and policies for the management of agricultural research in small countries, which identified improved access to scientific information as a key part of effective agricultural research in small countries.